Von Tarschisch bis nach Indien. Die Integration der Iberischen Halbinsel in das Weltherrschaftsschema des Alten Orients und seiner Erben (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper discusses the eastern political and geographical de- mand for global empire —especially regarding the Western Mediterranean— from the neo-Assyrian kings to Alexander and the following western demand for global empire by the imitators of Alexander, i.e. from Hannibal, Pompey to the later-empire-rulers in Rome.
Keywords: Tarshish; Asarhaddon; Alexander; India; Melqart-Heracles; Hannibal; Pompey; Caesar; World-empire